MORTALITY BY CARDIOVASCULAR DISEASES IN THE STATE OF PARANÁ - Fernanda Sabini Faix Figueiredo; Rosana Rosseto de Oliveira; Rafaely de Cassia Nogueira Sanches; Thais Aidar de Freitas Matias; Cremilde Aparecida Trindade Radovanovic (Cogitare Enfermagem, 2018)
Objective: To analyze the trend in mortality from ischemic and cerebrovascular cardiovascular diseases by age and gender in the state of Paraná. Methodology: Ecological study of rates of mortality rates from cardiovascular diseases in the years 2000 to 2014, conducted in July 2016. Polynomial regression model was used for trend analysis. Results: There was a progressive increase in mortality rates with increasing age in both genders. Mortality rates were higher in the first triennium (2000-2002), except for cerebrovascular diseases in men aged 20-29 years and ischemic diseases in women in this age group. Conclusion: Given the high number of deaths from cardiovascular diseases in Paraná, with a trend of increased mortality from cerebrovascular diseases in the young male population, nursing activities at the various levels of care should be intensified to fight the risk factors in the referred population.